The Intersection of Citizenship and Freedom of Religion: Legal Challenges in a Multicultural Society - Syahrial Arif Hutagalung; Yessi Kurnia Arjani Manik; Maulana Akhyar Hanif (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2025)
This study investigates the correlation between citizenship status and religious freedom within Indonesia's multicultural society, emphasizing the legal obstacles encountered by religious minority groups. The methodology employed is a normative-doctrinal legal approach, analyzing several national legal instruments, Constitutional Court rulings, and literature on legal and human rights. The research findings indicate a discrepancy between constitutional provisions that ensure religious freedom and prevailing legal practices that are often discriminatory. For instance, restrictions persist that restrict access to civil registry and marriage for followers of faiths beyond the six recognized religions. Furthermore, the legal status of groups like Ahmadiyah and practitioners of indigenous traditions signifies a de facto exclusion from citizenship. The findings suggest that the Indonesian legal system has not yet adequately ensured the concept of non-discrimination within the context of an inclusive rule of law. This research advocates for the enhancement of the alignment between positive legal norms and constitutional ideals, as well as the facilitation of additional studies utilizing comparative and empirical methodologies to advance equitable legal protection for minority groups.